A pattern of ocular morbidity of patients attending a clinic in Western Nepal - Tuladhar, S; Dhakal, S (International Journal of Infection and Microbiology, 2012)
INTRODUCTION: Very few reports exist regarding the causes of ocular morbidity in Western Nepal. The study is performed to identify the causes of ocular morbidity in a clinic at Waling in Western Nepal. MATERIALS AND METHODS: A retrospective study was done by reviewing the case records of all patients attending the eye clinic at Waling from August 2010 to August 2011. RESULTS: The study included 915 patients, 617 were females (67.5%), and 298 were males (32.5%). Refractive error was the most common ocular morbidity accounting 26.8% followed by conjunctivitis 20.6%, cataract 11.8%, pterygium 6%, chalazion/stye 4%, ectropion/entropion 3.9%, keratitis 3.8%, dry eyes 2.8%, and corneal opacities 2.3%. CONCLUSIONS: The study gives a picture and patterns of ocular disease in Western Nepal which will be helpful in planning & management of ocular health programmes in Nepal. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6941 Int J Infect Microbiol 2012;1(1):34-37